Employability Skills in TVET Curriculum in Nigeria Federal Universities of Technology. (24th August 2015) - Ismail, Sarimah; Mohammed, Dahiru Sale
Abstract: In the 21 st century, employability skill is the most required skill besides technical knowledge in an attempt to compete for employment and sustain job at the industrial global market. However, Nigerian TVET graduates are not equipped with the employability skills needed by the industries and as a result, they are not ready to enter into workforce. This concept paper is written to discuss how the curriculum of one of TVET programmes at the Federal Universities of Technology in Nigeria, which is Electrical Technology Education has contributed to this issue. Analytical review on Electrical Technology Education programme curriculum showed that the curriculum gave less attention to practice based courses that provide skills of the programme than theory based courses and no course in the programme curriculum that directly teaches good attitudes and traits. As a result, there is lack of incorporation of employability skills such as Problem solving and decision making, Lifelong learning and Competencies amongst the graduates. Other issues discussed are the need of employability skills in TVET curriculum of Nigeria, employability skills, Electrical Technology Education in Nigeria, and the analysis of Electrical Technology Education curriculum in Nigeria The last part of this paper is recommendation for the curriculum of Electrical Technology Education to be designed with equal number of theory and practice courses by giving emphasize on all eleven generic skills, good traits and attitudes.